Demography of Clethrionomys gapperi in different habitats - Bondrup-Nielsen, Søren (Canadian Journal of Zoology, 1987)
Theoretical considerations indicate that habitat heterogeneity may affect vole population density dynamics. The greater the degree of habitat heterogeneity, the greater the likelihood that a vole population will show stable rather than cyclic density dynamics. A livetrapping study of Clethrionomys gapperi was conducted near Lesser Slave Lake, Alberta, Canada, to examine the effect of habitat on demography and behaviour on this species. Voles in different habitat types differed in spring and late summer density, persistence, ratio of immature to total recruits, transiency, and home range size. There was no difference in litter size of voles among habitat types. Clethrionomys gapperi is not a cyclic species and sexually mature females are territorial. In this study demography of vole populations differed greatly among habitat type and only on one grid in 1 year did the density of sexually mature females reach saturation. Therefore, in each year there was always rooom for territorial establishment of females born in that year. This is unlike the situation for cyclic populations of Clethrionomys spp. in which there is no room for territorial establishment of such females during the peak population phase.